Classroom Environment: a literature review - MacAulay, Dolina J. (Educational Psychology, 1990)
The literature on classroom environment from 1980 onwards is reviewed. Special reference is made to elementary settings and to students with behavioral deficits. Structure and organization, cognitive processes, student characteristics and teacher characteristics are all seen as being capable of modification. It is concluded that the achievement of a match between students' preferences and instructional settings is a necessary condition for maximizing their cognitive, social and affective outcomes.
Keywords: BE:RELEVANT